Book Review: A Journey in Service By Ibrahim B. Babangida - ADEBODUN, Olalekan Henry (Àgídìgbo: ABUAD Journal of the Humanities, 2025)
Ibrahim Badamasi Babangida’s A Journey in Service is a landmark autobiographical account that offers a deeply reflective and historically grounded narration of his personal evolution from a humble upbringing in Minna to the zenith of Nigeria’s political leadership. Published in 2025, the work is structured with meticulous care, segmenting Babangida’s life into five major thematic parts: early years, military career, governance, retirement, and reflective epilogue. The author represents a significant contribution to the autobiographical and political literature of post-independence Nigeria. As Nigeria’s former military president (1985–1993), Babangida remains a pivotal, albeit polarising, figure in the country’s modern history. His memoir offers insight into the motivations, dilemmas, and philosophies that underpinned his leadership during a particularly volatile era. The work serves not only as a record of events but also as a rhetorical attempt to reshape public perception of his controversial policies and decisions.